Proceso de atención de enfermería en paciente escolar, con dolor pélvico relacionado con vaginitis. - Cachupud Cuji, María Verónica (2021)
Vaginitis is a gynecological problem that can occur at any age in women, it is an infection of the vagina that occurs between 17 to 50%, in prepuberculosis. There are several causes for which this pathology manifests itself, (v. Bacterial, vaginal candidiasis, trichomoniasis). The main symptom is itching, thick white discharge, erythema. “Vaginitis can be diagnosed by physical examination, culture examination, laboratory analysis, pH test. Generally it is treated with an antifungal cream or suppository, avoid using softeners, perfumed soaps or irritants to clean the genital area. " (MFMER, 2019). The basis of this clinical case is specifically focused on the development of the nursing care process in a school patient, who was hospitalized in the pediatric area for presenting, pelvic abdominal pain, headache, hyperthermia of more or less 12 hours of evolution. Immediately the inspection, evaluation, laboratory tests are carried out. Where timely data was obtained to treat the presented pathology. Patient is admitted under medical surveillance and under the care of the nursing staff.